THE ROLE OF THE UNITED NATIONS SECURITY COUNCIL AS REGARDS DISARMAMENT AND NUCLEAR NON-PROLIFERATION (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to analyse the role played by the United Nations SecurityCouncil as regards nuclear disarmament and non-proliferation.It can be seen how the body responsible for maintaining peace withinthe universal organisation has gathered more power and authority inthis area over time. Moreover, this paper discusses the attitude adoptedby the Security Council to the different cases of nuclear proliferation.Its goal is twofold: to examine to what extent the positions of the differentmembers of the Security Council are able to affect the Council’sactions, as well as to analyse their influence on the nuclear non-proliferationand disarmament regime.